Monitoring the Spread of Multidrug-Resistant Escherichia coli Throughout the Broiler Production Cycle - Victor Dellevedove Cruz; Danilo Henrique Rabaçal Alves; Jamile Kellen de Souza; Maísa Fabiana Menck-Costa; Bruno Henrique Dias de Oliva; Ana Angelita Sampaio Baptista; Alexandre Oba; Fabrizio Matté; Kácio Emílio Borges Baierle; Sérgio Paulo Dejato da Rocha; Kelly Cristina Tagliari de Brito; Benito Guimarães de Brito; et al. (Antibiotics)
The extensive use of antimicrobials in broiler production is changing the bird microbiota, fostering drug-resistant bacteria, and complicating therapeutic interventions, making the problem of multidrug resistance global. The monitoring of antimicrobial virulence and resistance genes are tools that have come to assist the breeding of these animals, directing possible treatments as already used in human medicine and collecting data to demonstrate possible dissemination of multidrug-resistant strains that may cause damage to industry and public health. This work aimed to monitor broiler farms in southern Brazil, isolating samples of E. coli and classifying them according to the profile of resistance to antimicrobials of interest to human and animal health. We also monitored the profile of virulence genes and conducted an epidemiological survey of possible risk factors that contribute to this selection of multidrug-resistant isolates. Monitoring was carried out on farms in the three southern states of the country, collecting samples of poultry litter, cloacal swabs, and beetles of the species Alphitobius diaperinus, isolating E. coli from each of these samples. These were evaluated by testing their susceptibility to antimicrobials of animal and human interest; detecting whether the samples were extended-spectrum β-lactamase enzyme (ESBL) producers; and when positive, selected for genotypic tests to identify resistant genes (CTX-M, TEM, and SHV) and virulence. Among the antimicrobials tested, enrofloxacin and ciprofloxacin demonstrated some of the highest frequencies of resistance in the isolated strains, with significant statistical results. The use of these antimicrobials increased the likelihood of resistance by over three times and was associated with a 1.5-fold higher probability of multidrug resistance. Of all isolates, 95% were multidrug-resistant, raising concerns for production and public health. Among 231 ESBL-positive samples, the CTX-M1 group predominated.